2013
DOI: 10.3233/prm-130233
|View full text |Cite
|
Sign up to set email alerts
|

Facilitated tucking on pain in pre-term newborns during neonatal intensive care: A single blinded randomized controlled cross-over pilot trial

Abstract: PURPOSE: To determine the effect of facilitated tucking (FT) on pain in preterm newborns during heel stick procedure done as a part of neonatal intensive care. METHODS: This randomized controlled cross-over pilot study included 20 preterm newborns of both sexes between gestational ages (GA) of 28 and 36 weeks based upon the eligibility criteria. Pain was measured using Premature Infant Pain Profile (PIPP) following both heel stick with FT and without FT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…This result is in line with Liaw et al's (2012) study, which reported that there was a significantly shorter duration of crying in a group of premature infants who were provided with oral sucrose, non-nutritive sucking and facilitated tucking during the heel stick procedure than in a group who were provided with standard care. Sundaram et al (2013) also reported lower levels of pain in preterm infants who were provided with facilitated tucking during the heel stick procedure. A combination of facilitated tucking and music also reduced pain levels significantly and shortened the duration of crying in their intervention group (68.5 seconds) in comparison with the control group (105 seconds) (Zubaidah & Naviati, 2015).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This result is in line with Liaw et al's (2012) study, which reported that there was a significantly shorter duration of crying in a group of premature infants who were provided with oral sucrose, non-nutritive sucking and facilitated tucking during the heel stick procedure than in a group who were provided with standard care. Sundaram et al (2013) also reported lower levels of pain in preterm infants who were provided with facilitated tucking during the heel stick procedure. A combination of facilitated tucking and music also reduced pain levels significantly and shortened the duration of crying in their intervention group (68.5 seconds) in comparison with the control group (105 seconds) (Zubaidah & Naviati, 2015).…”
Section: Discussionmentioning
confidence: 86%
“…This finding corresponds with that of Reyhani, Mohebi, Boskabadi, Gholami, and Ghanbarabadi (2012), who reported that there was a significant difference in pulse rate and oxygen saturation in a group which had been provided with facilitated tucking during blood collection (p= 0.001). A study conducted by Sundaram, Shrivastava, Pandian, and Singh (2013) also revealed a significantly lower pulse rate during a 120-second relaxation phase in infants who had received facilitated tucking during blood collection by heel stick.…”
Section: Discussionmentioning
confidence: 96%
“…The adverse effects of oral sucrose include a reduction in ATP synthesis and phosphate depletion due to poorly regulated fructose metabolism [9,10]. Facilitated tucking is the gentle positioning of preterm infants with arms and legs in a flexed, midline position close to the body, while either in a side-lying or prone position [11]. Facilitated tucking has been documented to reduce the behavioral and physiological signs of pain, as evidenced by a reduction in pain scores and heart rate [11,12].…”
Section: Methodsmentioning
confidence: 99%
“…Facilitated tucking is the gentle positioning of preterm infants with arms and legs in a flexed, midline position close to the body, while either in a side-lying or prone position [11]. Facilitated tucking has been documented to reduce the behavioral and physiological signs of pain, as evidenced by a reduction in pain scores and heart rate [11,12]. This study's painful procedure is a clinically required heel lance, which refers to a puncture of the newborn's heel for a blood glucose test using a specially designed lancet.…”
Section: Methodsmentioning
confidence: 99%
“…38 Because the primary outcomes of studies related to swaddling and containment are less commonly summarized, an illustrative overview of studies on facilitated tucking in of (pre)term neonates (either or not combined or compared with other complementary interventions) is provided in Table 1. 37,[39][40][41][42][43][44][45][46][47][48] Most of these studies were not blinded, had a crossover design, and order effects are rarely reported. However, the available evidence suggests a modest reduction in pain with a faster return of physiologic fluctuations to baseline.…”
Section: Swaddling and Containmentmentioning
confidence: 99%